Evaluation of hypoglycemic status and causative factors in neonatal sepsis - Islam, Md Zahirul; Aklima, Jannatul; Yesmin, Farhana; Islam, Mohammad Sayedul; Chakma, Kanchan; Alauddin, Mohammad; Hasan Bhuiyan, Robiul (International Journal of Contemporary Pediatrics, 2017)
Background: Very few studies have been reported on hypoglycemic status, hematological parameters and causative organisms of neonatal sepsis in different regions of Bangladesh. Hence, present study was conducted in the Chittagong city of Bangladesh. Methods: The study was conducted on 106 neonates (0 to 28 days of age) in Chattagam Maa-Shishu O General Hospital, Bangladesh. The questionnaire was developed to get relevant information of the neonates. Blood from neonates were subjected to routine investigations like blood glucose, CRP, hematological parameters, blood culture and bacterial identification. Results: Among 106 neonates with sepsis, 68 presented early onset neonatal sepsis (EONS) and 38 presented late onset neonatal sepsis (LONS). Fifty-one neonates had low birth weight (2500 g or less), 18 had very low birth weight (1500 g or less) and 22 were preterm. The most prevalent clinical features were reluctant to feed (56), hyperthermia (31) and hypotonia (22). Thirty-three neonates had neutropenia (<54%) and 62 had higher neutrophil count (>62%). Biochemical analysis showed 52 had higher C-reactive protein levels. Investigation of hypoglycemic status revealed that there were different types of neonatal sepsis, i.e. 77 neonates were hypoglycemic (<45 gm/dl), and among them EONS and LONS were 59 and 18, respectively. Thirty-three neonates had positive blood culture for bacteria. Among them, Klebsiella spp. accounted for 10 of the total isolates followed by Acinetobacter spp. 8. The Gram-positive and negative bacteria were found in 7 and 26, respectively. Conclusions: Hypoglycemia was associated with neonatal sepsis as an exacerbating factor.